Answer:
- <em>m</em> =
- <em>μ</em> = 20
- <em>σ </em>= 20
The probability that a person is willing to commute more than 25 miles is 0.2865.
Step-by-step explanation:
Exponential probability distribution is used to define the probability distribution of the amount of time until some specific event takes place.
A random variable <em>X</em> follows an exponential distribution with parameter <em>m</em>.
The decay parameter is, <em>m</em>.
The probability distribution function of an Exponential distribution is:
![f(x)=me^{-mx}\ ;\ m>0, x>0](https://tex.z-dn.net/?f=f%28x%29%3Dme%5E%7B-mx%7D%5C%20%3B%5C%20m%3E0%2C%20x%3E0)
<u>Given</u>: The decay parameter is, ![\frac{1}{20}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B20%7D)
<em>X</em> is defined as the distance people are willing to commute in miles.
- The decay parameter is <em>m</em> =
. - The mean of the distribution is:
. - The standard deviation is:
Compute the probability that a person is willing to commute more than 25 miles as follows:
![P(X>25)=\int\limits^{\infty}_{25} {\frac{1}{20} e^{-\frac{1}{20}x}} \, dx \\=\frac{1}{20}|20e^{-\frac{1}{20}x}|^{\infty}_{25}\\=|e^{-\frac{1}{20}x}|^{\infty}_{25}\\=e^{-\frac{1}{20}\times25}\\=0.2865](https://tex.z-dn.net/?f=P%28X%3E25%29%3D%5Cint%5Climits%5E%7B%5Cinfty%7D_%7B25%7D%20%7B%5Cfrac%7B1%7D%7B20%7D%20e%5E%7B-%5Cfrac%7B1%7D%7B20%7Dx%7D%7D%20%5C%2C%20dx%20%5C%5C%3D%5Cfrac%7B1%7D%7B20%7D%7C20e%5E%7B-%5Cfrac%7B1%7D%7B20%7Dx%7D%7C%5E%7B%5Cinfty%7D_%7B25%7D%5C%5C%3D%7Ce%5E%7B-%5Cfrac%7B1%7D%7B20%7Dx%7D%7C%5E%7B%5Cinfty%7D_%7B25%7D%5C%5C%3De%5E%7B-%5Cfrac%7B1%7D%7B20%7D%5Ctimes25%7D%5C%5C%3D0.2865)
Thus, the probability that a person is willing to commute more than 25 miles is 0.2865.
The y intercept is always c (-5) and to the axis of symmetry u do -b/2a which is -1 and the vertex is (-1,10) because u pug in -1 into the equation. lmk if it’s right!
Simplest fraction form is "3/4"
Answer:(2,0) x=2,y=0
Step-by-step explanation:
Let's solve your system by elimination.
−x+y=−2;2x−3y=4
Multiply the first equation by 2,and multiply the second equation by 1.
2(−x+y=−2)
1(2x−3y=4)
Becomes:
−2x+2y=−4
2x−3y=4
Add these equations to eliminate x:
−y=0
Then solve−y=0 for y:
−y=0
−y/−1 =0/−1
(Divide both sides by -1)
y=0
Now that we've found y let's plug it back in to solve for x.
Write down an original equation:
−x+y=−2
Substitute0foryin−x+y=−2:
−x+0=−2
−x=−2(Simplify both sides of the equation)
−x/−1 = −2/−1
(Divide both sides by -1)
x=2
- 6b > 42 or 4b > - 4
Divide by - 6. Divide by 4.
b < - 7 Or b > - 1